KEEFEKTIFAN THINK-PAIR-SHARE UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA MENGENAI KONSEP DASAR HUBUNGAN MASYARAKAT - Oktarina, Nina (Fakultas Ekonomi, Universitas Negeri Semarang, 2010)
Intention of research this is to improve quality of study of public relations, to increase the spirit of learning student, to uplift skill teacher in developing model and study media and to increase the achievement learn student. This research is research of class action which is consisted of three cycle. Result of research show achievement learn natural student of improvement in each its cycle. learn student of before applying of method Think-Pair-Share 0%, after applying of method Think-Pair-Share, learn from student after conducted by a final test is 76,67%. Enthusiasm, livelines and student cooperation in course of study of 1-4 result is good ( 3,39). Perception result hit skill teacher in study management by using method Think-Pair-Share with 1-4 showing good result with rate from cycle 1, cycle 2, and cycle 3 is 3,38. The score represent rate from entire/all aspect perceived at three